RELIGIJNOŚĆ MATURZYSTÓW PUŁAWSKICH W PROCESIE PRZEMIAN - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this article, we will discuss a few selected issues related to the religiosity of Puławy high school graduates, and these are: religious affiliation, Catholicism and Polishness, and self-declarations of religious practices. The study was conducted at three intervals 1994, 2008/2009, 2016. Our main research hypothesis assume that the young people in the last year of high school are already in advanced stage of adolescence, partly becoming independent from their family of origin, and their main interests and activities move beyond the family. At that stage of their development, the young people recognize precisely their life prospects and at the same time increasingly determine their hierarchy of values and moral autonomy. The distortion, and sometimes the disintegration of family values and norms occur, and these increasingly affect the behavior of individuals. Significant changes in religiosity refer to religious practices (decline in regular practice in 1994-2016 was 20.7%).